2009
DOI: 10.4049/jimmunol.0801826
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine Receptor CCR7 Contributes to a Rapid and Efficient Clearance of Lytic Murine γ-Herpes Virus 68 from the Lung, Whereas Bronchus-Associated Lymphoid Tissue Harbors Virus during Latency

Abstract: Murine γ-herpes virus 68 is a natural rodent pathogen closely related to the human γ-herpes viruses Kaposi’s sarcoma-associated herpes virus and EBV. By intranasally infecting wild-type and CCR7-deficient mice, we investigated whether CCR7 is necessary for viral clearance from the lung and the establishment of latency. We found during the lytic phase of infection that inflammation in lungs of CCR7−/− mice was more severe and viral load significantly higher compared with wild-type littermates. In addition, acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 36 publications
1
28
1
Order By: Relevance
“…Our findings are similar to those of a study in a murine Listeria monocytogenes infection model, where efficient priming of CD8 ϩ T cells was found to be Ccr7 independent (36). In contrast in gamma herpesvirus 68 -infected mice, a temporally efficient activation of T cells and viral clearance were Ccr7 dependent (37). Thus, the role of Ccr7 in T cell activation appears to be context and model dependent.…”
Section: Discussionsupporting
confidence: 80%
“…Our findings are similar to those of a study in a murine Listeria monocytogenes infection model, where efficient priming of CD8 ϩ T cells was found to be Ccr7 independent (36). In contrast in gamma herpesvirus 68 -infected mice, a temporally efficient activation of T cells and viral clearance were Ccr7 dependent (37). Thus, the role of Ccr7 in T cell activation appears to be context and model dependent.…”
Section: Discussionsupporting
confidence: 80%
“…CCL19 and CCL21 expression has been identified in peripheral organs, such as the lung (27,43), but their role in host defense is not fully understood. Previous studies employing models of pulmonary infection have shown that CCR7 deficiency leads to impaired host defense (1,6,15,18,19,22,31). However, we demonstrated that CCR7 deficiency FIG.…”
Section: Discussioncontrasting
confidence: 52%
“…CCL19 and CCL21 are expressed primarily in secondary lymphoid organs, but they are also expressed in other tissues, such as the gastrointestinal tract, kidney, and lung (27,43). Previous studies demonstrated that disruption of cellular interactions coordinated through CCR7 impaired T cell function and increased susceptibility to viral infections (10,12,19,29). These results were attributed to disruption of lymph node architecture and impaired T cell and DC migration to the lymph node, which prevented efficient antigen presentation to naïve T cells.…”
mentioning
confidence: 88%
See 2 more Smart Citations